HSPB7 gene polymorphism associated with anthropometric parameters of obesity and fat intake in a Central European population - Pavlová, Tereza; Novák, Jan; Zlámal, Filip; Bienertová-Vašků, Julie (Central European journal of public health, 2018)
OBJECTIVE: Heat shock proteins act as chaperones at the molecular level and therefore they have been investigated in numerous diseases associated with oxidative stress, including obesity. The aim of this study was to investigate the possible associations of genetic variability in the 3´-untranslated region of the HSPB7 gene (rs1048261) with anthropometric and dietary parameters in a cohort of lean and obese Central European subjects. METHODS: A total of 708 Central European Caucasian individuals were enrolled in this study, 415 obese subjects and 293 non-obese subjects. The rs1048261 genotypes were established using a conventional PCR-based methodology. RESULTS: Significant differences were observed in the total daily fat intake between subjects with AT and TT genotypes (82.6 ± 29.2 g vs. 74.1 ± 31.3 g, p = 0.023) and also borderline significance in daily proportion of fat in the diet between AA and TT genotypes (36.0 ± 4.4% vs. 33.3 ± 5.9%, p = 0.061). Based on the linear regression model we found association between rs1048261 genotype and body fat percentage. CONCLUSIONS: To the best of our knowledge, this is the first study which reports an association of defined genetic variability in the HSPB7 gene, rs1048261, with obesity and its associated anthropometric characteristics and dietary composition.
Keywords: HSP27 Heat-Shock Proteins; Genotype; Europe; dietary composition; Anthropometry; rs1048261; dietní tuky; Obesity; lidé; Evropa; genotyp; proteiny tepelného šoku HSP27; antropometrie; fat intake; dieta; HSPB7; obezita; Diet; polymorfismus genetický; polymorphism; obesity; Polymorphism, Genetic; Dietary Fats; Humans